The Role and Impact of Seasonal Food Availability on the Dietary Patterns of Lactating Women: Evidence from the Kashkadarya Region of Uzbekistan - Shohimardonova Aziza Boynazar qizi (American Journal of Biology and Natural Sciences, 2026)
Background: Maternal nutrition during lactation is essential for maintaining maternal health, supporting breast milk production, and ensuring optimal infant growth and development. Seasonal food availability may influence dietary patterns, particularly in rural communities. Objective: This study aimed to assess the spring-season dietary patterns of lactating women in the Chiroqchi and Kasbi districts of the Kashkadarya region and to identify age-related differences in food consumption. Methods: A cross-sectional survey was conducted among 450 lactating women using a structured questionnaire. Data on the consumption of major food groups, including meat, dairy products, cereals and legumes, fruits, vegetables, eggs, fish, and green leafy vegetables, were collected and analyzed as percentages according to age groups. Results: Cereals and legumes were the most frequently consumed food group, accounting for 98.0% and 99.0% of intake among women aged 18–29 and 30–39 years, respectively. Dairy products were consumed by more than half of the participants, while meat consumption was higher among older women. Fruit and vegetable intake remained low in both age groups, indicating limited dietary diversity. Fish consumption was moderate, whereas green leafy vegetables were not consumed by the surveyed women. Conclusion: The diets of lactating women during the spring season were predominantly cereal-based and lacked sufficient amounts of fruits, vegetables, and other nutrient-rich foods. These findings highlight the need for nutrition education programs and interventions aimed at improving dietary diversity and promoting balanced nutrition among lactating women in rural areas.